Assessing the Effectiveness of Outreach Measures at a Student-Run Free Clinic - Shalmali Mirajkar; Jay J Byrd; Currey M Zalman; Margarita I Pipinos; Emily Evans; Jenenne Geske; Melanie S Menning (Journal of Student-Run Clinics, 2024)
Background: Student-run, free clinics (SRFCs) seek innovative and cost-effective outreach strategies to recruit new patients and raise awareness of their services. The current literature presents several approaches to increase community engagement, but the formal evaluation of these outreach efforts is scarce. The present study aims to fill this gap by measuring the effectiveness of outreach efforts on patient visits, which was implemented over the past year at an SRFC in Omaha, Nebraska.Methods: A retrospective review of clinic traffic and outreach efforts deployed at our SRFC for 13 months. Six formal outreach methods were identified and included in the analysis. Patient recruitment was measured by calculating the difference in total patient volume 30 days before and after the implementation of an outreach effort. An effort’s efficacy was evaluated by calculating the financial expenses and time spent per patient recruited for the corresponding outreach methodology.Results: Two-thirds of the efforts resulted in increased patient volume, with the additional third being associated with decreased traffic. The most successful outreach effort, which resulted in an average increase of 9 patients, only required the investment of 0.67 hours  per patient, with no financial cost. The least successful effort required 2 hours and cost $11 per patient.Conclusions: This study provides an approach to evaluate the efficacy of outreach efforts to increase patient recruitment at our SRFC. The financial expenditure, volunteer time, and corresponding efficacy of previous efforts should be considered prior to their re-utilization. Additionally, these findings support future prospective tracking of patient recruitment and retention data to optimize the quality and quantity of patient care. By addressing these challenges, clinics can better serve their target population and fulfill their mission of providing quality medical care to underserved communities.